Insects’ oil as an alternative lipid source: extraction, composition, and potential applications - Mirghani, Mohamed Elwathig Saeed; Yassin, Atif A. A.; Daoud, Jamal I. (AIJR Publisher, 2025)
Insects offer a promising solution as a source of food due to their fascinating life cycles. Their rapid turnover is a marvel of efficiency. Insects have the ability to adapt and thrive across different environmental conditions. Many types of insects are found to have high oil contents and efficient conversion of organic matter into valuable nutrients. However, the utilization of insect as an oil source raises questions regarding its compliance with Halal and Kosher dietary laws, which are significant considerations for Muslim and Jewish communities, respectively. In this review we are trying to discusses the potential uses of insect farming and processing technologies aimed at addressing concerns related to insects as an alternative source for vegetable oils, considering their implications for adhering to religious dietary requirements. Also, it is important to address the issue of insect-derived oil and the potential challenges and opportunities in market acceptance. It is mainly due to religious guidelines governing permissible foods; especially regarding the key factors influencing the Halal and Kosher status of insect-derived products. Overall, this review provides valuable insights into the intersection of insect oil production by addressing religious concerns and promoting transparency in production processes. Moreover, the integration of insect-derived oils into mainstream markets can be facilitated, offering sustainable solutions to the growing demand for edible oils & fats, respecting diverse cultures, religions and values.